2021
DOI: 10.1182/blood.2020008743
|View full text |Cite|
|
Sign up to set email alerts
|

KDM5 inhibition offers a novel therapeutic strategy for the treatment of KMT2D mutant lymphomas

Abstract: Loss-of-function mutations in KMT2D are a striking feature of the germinal centre (GC) lymphomas, resulting in decreased H3K4-methylation and altered gene expression. We hypothesised that inhibition of the KDM5 family, which demethylates H3K4me3/me2, would re-establish H3K4-methylation and restore the expression of genes repressed upon loss of KMT2D. KDM5-inhibition increased H3K4me3 levels and caused an anti-proliferative response in vitro, which was markedly greater in both endogenous and CRISPR-edited KMT2D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Loss‐of‐function mutations in the epigenetic regulators, CREBBP and KMT2D , are inherently more challenging to reverse. However, promising pre‐clinical data evaluating histone deacetylase 3 (HDAC3) inhibition in CREBBP ‐mutated lymphoma 38 and lysine demethylase 5 (KDM5) inhibition in KMT2D ‐mutated lymphomas 92 lend support to the potential of inhibiting the opposing or antagonistic partners of these disrupted epigenetic regulators as a means of restoring the balance of global histone acetylation or methylation respectively. Taking a contrasting approach, a dependence of CREBBP ‐mutated lymphoma cells on residual EP300 function represents a synthetic lethality relationship that has been shown to be exploited in vitro via dual CREBBP/EP300 inhibition 30 .…”
Section: Harnessing Biology To Novel Therapeuticsmentioning
confidence: 99%
“…Loss‐of‐function mutations in the epigenetic regulators, CREBBP and KMT2D , are inherently more challenging to reverse. However, promising pre‐clinical data evaluating histone deacetylase 3 (HDAC3) inhibition in CREBBP ‐mutated lymphoma 38 and lysine demethylase 5 (KDM5) inhibition in KMT2D ‐mutated lymphomas 92 lend support to the potential of inhibiting the opposing or antagonistic partners of these disrupted epigenetic regulators as a means of restoring the balance of global histone acetylation or methylation respectively. Taking a contrasting approach, a dependence of CREBBP ‐mutated lymphoma cells on residual EP300 function represents a synthetic lethality relationship that has been shown to be exploited in vitro via dual CREBBP/EP300 inhibition 30 .…”
Section: Harnessing Biology To Novel Therapeuticsmentioning
confidence: 99%
“…All the above studies have shown that H3K4me3 played a role in promoting cancer. However, H3K4me3 demethylation caused by the loss of KMT2D function in the germinal center of lymphoma led to rapid tumor progression, and the re-establishing of H3K4 trimethylation caused significant tumor growth inhibition ( 49 ). It was also reported that KDM5B downregulated PTEN expression by suppressing the accumulation of H3K4me3 in the PTEN promoter region so as to enhance the radioresistance of NSCLC ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the OXPHOS inhibitor IACS-010759 did not have a significant selective inhibitory effect on the proliferation of KMT2D-deficient cancer cells compared to that of KMT2D-WT cancer cells [32,33]. Interestingly, pharmacological inhibition of the KDM5 family of H3K4 demethylases diminished tumorigenic growth of KMT2D-mutant lymphoma cells, as certain KDM5 family members can antagonize the function and methylation activity of KMT2D [84]. Other study has shown that KMT2D deficiency sensitizes different types of syngeneic tumors (including lung tumor, bladder tumor, breast tumor, and melanoma) to anti-PD1 [49], suggesting that anti-PD1 may have a stronger inhibitory effect on KMT2D-mutant tumors than on KMT2D-WT tumors.…”
Section: Therapeutic Opportunities For the Treatment Of Kmt2d-deficient Tumorsmentioning
confidence: 95%